2013
DOI: 10.1248/bpb.b13-00611
|View full text |Cite
|
Sign up to set email alerts
|

Use of the <i>psbA-trnH</i> Region to Authenticate Medicinal Species of Fabaceae

Abstract: Fabaceae is a huge family that contains a large number of medicinal plants, many of which are commonly used in Chinese traditional medicine. However, traditional taxonomy has not been able to meet the complicated demands of species discrimination within Fabaceae. Thus, we employed a famous DNA barcode, the psbA-trnH region, to discriminate commonly used medicinal species of the family Fabaceae. Here, the psbA-trnH regions derived from 152 samples were amplified. These samples represented 104 Fabaceae medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…Many researchers have reported that the intra-specific variation of psbA-trnH region is very low while the inter-specific divergence is very large in a wide variety of plants (Gao et al 2013;Ma et al 2010;Yang et al 2011;Yao et al 2009). Similar results were found in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many researchers have reported that the intra-specific variation of psbA-trnH region is very low while the inter-specific divergence is very large in a wide variety of plants (Gao et al 2013;Ma et al 2010;Yang et al 2011;Yao et al 2009). Similar results were found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, their identification based on morphological characteristics, which are similar, is extremely difficult. In fact, the psbA-trnH region has been used as a DNA barcode to authenticate various plants with similar morphological traits (Chen et al 2010;Gao et al 2013;Ma et al 2010;Yang et al 2011;Yao et al 2009). In the present work, we used for the first time the chloroplast psbA-trnH region for barcoding Physalis species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITS2 region was used to identified dicotyledons, monocotyledons, gymnosperms and ferns, the success rates was different [ 13 ]. Fabaceae is a huge family, among them 91.3% of 104 Fabaceae medicinal species was identified successfully by using of trn H -psb A sequences [ 14 ]. Data from trn H -psb A region were analysed to illuminate molecular evolution of Maghrebian Medicago species and reveal high interspecific diversity and low intraspecific variation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…15) DNA barcoding has since been successfully applied towards the traceability of many herb medicines. [16][17][18][19][20][21][22] Additional candidate DNA barcoding genes in seed plants, which are used for identification of Chinese medicines and to confirm the identities of the original plants, are currently providing a basis for identifying Phellodendri Cortex.…”
mentioning
confidence: 99%